The management of quality costs analysis model - Holota, Tomáš; Hrubec, Jozef; Kotus, Martin; Holienčinová, Mária; Čapošová, Eva (Serbian Journal of Management, 2016)
This article proposes a comprehensive introduction into the analysis and calculating costs and identifies the different areas of activities in company which can lead to improving the quality and reducing costs by using the PAF cost model. The basic precondition for quality improvement in company is understanding of the process and its control with regard to the objectives which should be achieved. PAF model is the most frequently used model for the quality costs analysis at present. In today’s competitive environment, all organizations consider as the first priority, provide to customers the highest quality for the best price, what can be achieved by setting optimal quality costs.